Rancang Bangun Sistem Informasi Manajemen Arsip Berbasis Web Pada Rumah Sakit Bedah Surabaya - Pascapraharastyan, Rizki Alfiasca; Supriyanto, Antok; Sudarmaningtyas, Pantjawati (Jurnal JSIKA, 2014)
Archives is an important documents in Rumah Sakit Bedah Surabaya (RSBS) for support in decision-making can also be used as evidence when problems occur and can also be made into accountability and bureaucratic transparency at the RSBS. Considering the importance of archives in rsbs then archives should not be damaged, lost and distribution of archives should be punctual to the destination department. But the conditions in RSBS archives frequent damage, lost and the distribution of an archive of being late. To overcome the obstacles in the archiving, the archives needs to be converted into digital data archives to minimize damage, loss of archives and can be distributed in a timely manner to the destination department. With this requirement it needs to make archive management information system in the RSBS. Archive management information systems have been tested to thirty users with questionnaires using likert scale and assessment testing information systems directly. Based on the results of questionnaires and tests, obtained a score ratings average 4.17 and archives can converted into Â digital archives and can distribute the archive in a punctual manner to the destination department . So it can be concluded that the archive management information systems can be used to manage the archive RSBS.